FORM OF A MIXED MARRIAGE - STAWNIAK, HENRYK (Prawo Kanoniczne, 2019)
The article is an attempt to show the form of entering into a mixed marriage in the context of changes in canonical marriage law and the possibility of dispensation from form. The new §3 can. 1108 of KPK in communication with can.1127 and justifies why only a priest can assist and bless marriage when one party belongs to the Eastern Community, excluding a deacon and a lay person, and an attention is paid to entities that can grant a dispensation. The meaning of the new §3 can. 1116 is also explained in the form of an extraordinary marriage with the extended rights of the Catholic ordinary of the place. In the final part, the issue of legal value and the function of the form of marriage in the context of the formal act of leaving the Church are being addressed.